Response of Chloris truncata to moisture stress, elevated carbon dioxide and herbicide application - Weller, S. L. (Sci Rep, 2019)
Herbicide resistance has been observed in Chloris truncata, an Australian native C(4) grass and a summer-fallow weed, which is common in no-till agriculture situations where herbicides are involved in crop management. To investigate the role of drought and increased atmospheric carbon dioxide (CO(2)) in determining weed growth, three trials were conducted using a ‘glyphosate-resistant’ and a ‘glyphosate-susceptible’ biotype. The first two trials tested the effect of herbicide (glyphosate) application on plant survival and growth under moisture stress and elevated CO(2) respectively. A third trial investigated the effect on plant growth and reproduction under conditions of moisture stress and elevated CO(2) in the absence of herbicide. In the first trial, water was withheld from half of the plants prior to application of glyphosate to all plants, and in the second trial plants were grown in either ambient (450 ppm) or elevated CO(2) levels (750 ppm) prior to, and following, herbicide application. In both biotypes, herbicide effectiveness was reduced when plants were subjected to moisture stress or if grown in elevated CO(2). Plant productivity, as measured by dry biomass per plant, was reduced with moisture stress, but increased with elevated CO(2). In the third trial, growth rate, biomass and seed production were higher in the susceptible biotype compared to the resistant biotype. This suggests that a superior ability to resist herbicides may come at a cost to overall plant fitness. The results indicate that control of this weed may become difficult in the future as climatic conditions change.